DEVELOPMENT OF THE CULTURAL COMPETENCE OF HIGH SCHOOL TEACHING STAFF - Viktoriia Levchenko; Inna Forostiuk ("Scientific Information Agency "Science-technologies-information" LLC, 2020)
Components of cultural awareness: linguistic; intercultural; socio-cultural; personal. Research of the state of the development of teachers' cultural awareness (50 respondents) from ten institutions of higher education of Ukraine, which are the representatives of different directions and specialties. The study revealed a significant role of the subjectivepersonal component in the development of cultural competence. The conditions which promote development of cultural competence are defined as next: 1) orientation to preservation of sacred values; 2) eco-social and psychologically safe space; 3) support from higher education institutions; 4) presence of personal qualities, such as openness, communication, flexibility, tolerance, readiness for uncertainty, the desire for self-realization.